KAP STUDY OF MENSTRUAL PROBLEMS IN ADOLESCENT FEMALES IN AN URBAN AREA OF MEERUT - Katiyar, Kalpana; Chopra, Harivansh; Garg, Sunil Kumar; Bajpai, S K; Bano, Tanveer; Jain, Seema; Kumar, Arun (Indian Journal of Community Health, 2013)
Background: Menstruation is an important milestone that results in development of sexual and reproductive capacity of girls. Adolescent girls do not have adequate knowledge about the abnormalities and healthy practices to be followed during menstruation. Objective:To find out the knowledge, attitude, practices regarding menstruation and treatment seeking behaviour for menstrual problems in adolescent females.Material & methods: The present cross sectional study was carried out in an urban field practice area of Department of Community Medicine, LLRM Medical College, Meerut on adolescent girls. A sample of 384 was derived and girls were selected by systematic random sampling technique. Detailed information was collected on a predesigned and pretested questionnaire. Results:38.5% girls were aware of menstruation prior to its onset out of which 66.9% learned from their mother. Only 14.6% of the menstruating girls were aware of at least one menstrual disorder. Dysmenorrhoea was found to be the most frequently occurring problem (58.4%), followed by oligomenorrhoea (16.2%), menorrhagia (13.9%), premenstrual tension (13.6%), infrequent menstruation (12.3%) and polymenorrhoea (12.2%). Out of the 226(72.7%) girls having menstrual problems 77.9% did not seek any treatment for their problems. 55.2% of the menstruating girls were using sanitary pads during menstruation. Conclusion: The adolescent girls are not well prepared and do not have adequate information regarding menstruation which is an important event of life.